Está en la página 1de 2

# EVALUACION 2

## Resuelve las siguientes sumas de fracciones algebraicas con

Escribir el desarrollo paso a paso.

1.
=
= 2a /(a+1) (a-1)

2.
9/x+x-12

## = 2(x-3) +1(x-3)/(x+4)(x-3) = 2x-6+x-3/x+4x-3x-12 = 3x-

3.
= 3(2x+5) + 6(1-x) /(1-x)(2x+5) = 6x+15+6-6x/(1-x) (2x+5)
= 21 / (1-x) (2x+5)

4.
= x(x+y) + x(x-y) / (x-y) (x+y) = x+xy+x-xy/ (x-y) (x+y) =
2x (x-y) (x+y)

5.
= (m-2)(m+3) + (m-3)(m+2)/(m-3)(m-2) = m-2m+3m6+m-3m+3m-6/(m3) (m-2) = 2m-12/ (m-3) (m-2)

6.
= (x+y) (x+y) + (x-y) (x-y) /(x-y) (x+y) = x+xy+xy+y+xxy-xy+y/(x-y)(x+y) =
2x+y/(x-y) (x+y)

7.
= x(x-1) +(x+1) (x+1) / (x-1) (x+1) = x-x+x+x+x+1 =
2x+x+1/(x-1)(x+1)

8.
= 2(x+5) +1(3x) / (x-5) (x+5) = 2x+10+3x /(x-5) (x+5) =
5x+10/ (x-5) (x+5)

9.
= 1(3x+2y) + 1(x-y) / (3x+2y) (3x-2y) = 3x+2y+x-y =
4x-y/ (3x+2y)(3x-2y)

10.
(x+a) (x-3a) +1(3a-x) / (x+3a) (x-3a) = x+ax-3ax-3a
+3a-x = -2ax/(x+3a) (x-3 a)

11.
(1+a) =

## = a +a/ (1-a) (1+a) (1+a) = a(1+a) + a(1-a) /(1-a)(1+a)

2a/ (1-a)(1+a)(1+a)

12.
= 2b(a+b) +2a(a-b) /a(a-b) b(a+b) = 2ab+2b+2a-2ab
= 2b+2a/a(a-b) b(a+b)